2014
DOI: 10.4049/jimmunol.1400538
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Agonist and Antagonist Signaling through the IL-36 Receptor

Abstract: The IL-1 family consists of 11 cytokines that control a complex network of proinflammatory signals critical for regulating immune responses to infections. They also play a central role in numerous chronic inflammatory disorders. Accordingly, inhibiting the activities of these cytokines is an important therapeutic strategy for treating autoimmune diseases and lymphomas. Agonist cytokines in the IL-1 family activate signaling by binding their cognate receptor and then recruiting a receptor accessory protein. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 44 publications
2
78
2
10
Order By: Relevance
“…Our data provide a rational basis for the development of therapies specifically targeting these pathways, particularly the IL-36 system in GPP (48, 49). …”
Section: Discussionmentioning
confidence: 90%
“…Our data provide a rational basis for the development of therapies specifically targeting these pathways, particularly the IL-36 system in GPP (48, 49). …”
Section: Discussionmentioning
confidence: 90%
“…Modeling showed that the b4/5 and b11/12 loops in IL-36 likely interact directly with IL-1RAcP. The largest conformational differences between IL-36Ra and IL-36 are found in these two loops and likely explain how IL-36 agonists mediate recruitment of IL-1RAcP, while IL-36Ra does not [89].…”
Section: Il-36ramentioning
confidence: 95%
“…IL-1Ra and IL-36Ra act as competitive antagonists of IL-1 and IL-36, respectively, by binding to the receptors (Fig. 2B) in a manner that does not allow the recruitment of IL-1RAP (20,(38)(39)(40)(41)(42). Because two intracellular domains-one from the receptor and one from the receptoraccessory protein-are required for MyD88 docking ( Fig.…”
Section: Introduction To the Interleukin-1 Familymentioning
confidence: 99%